2012
DOI: 10.1021/nl302453x
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Blinking and Auger Recombination in Near-Infrared Type-II InP/CdS Nanocrystal Quantum Dots

Abstract: Non-blinking excitonic emission from near-infrared and type-II nanocrystal quantum dots (NQDs) is reported for the first time. To realize this unusual degree of stability at the single-dot level, novel InP/CdS core/shell NQDs were synthesized for a range of shell thicknesses (~1–11 monolayers of CdS). Ensemble spectroscopy measurements (photoluminescence peak position and radiative lifetimes) and electronic structure calculations established the transition from type-I to type-II band alignment in these heteros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
162
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(184 citation statements)
references
References 35 publications
13
162
1
1
Order By: Relevance
“…5,11 A relatively small lattice mismatch for epitaxial growth and a large conduction-/valence-band offset for band-alignment tuning are two important factors for the manipulation of nanoheterostructures, such as CdS/ZnSe, CdSe/ZnTe, CdSe/CdS, InP/CdS, and CdTe/CdS core/shell QDs. [11][12][13][14][15] The lattice parameters of bulk CdTe and CdS are 6.481 and 5.838 Å, respectively. 16 CdTe conduction-and valence-band energies (about 3.5 and 5.2 eV, respectively, below vacuum) are higher than those of CdS (about 3.7 and 6.3 eV, respectively, below vacuum) by 0.2 and 1.1 eV, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…5,11 A relatively small lattice mismatch for epitaxial growth and a large conduction-/valence-band offset for band-alignment tuning are two important factors for the manipulation of nanoheterostructures, such as CdS/ZnSe, CdSe/ZnTe, CdSe/CdS, InP/CdS, and CdTe/CdS core/shell QDs. [11][12][13][14][15] The lattice parameters of bulk CdTe and CdS are 6.481 and 5.838 Å, respectively. 16 CdTe conduction-and valence-band energies (about 3.5 and 5.2 eV, respectively, below vacuum) are higher than those of CdS (about 3.7 and 6.3 eV, respectively, below vacuum) by 0.2 and 1.1 eV, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The diffraction peaks observed for the InP CQDs agree well with the expected peak positions and relative intensities. Dennis et al 18 reported that for 'giant' InP/CdS CQDs, with shells that were up to 4 nm thick, the CdS forms in its more thermodynamically stable hexagonal phase. However, here the diffraction peaks are little changed on the addition of the shell, and are consistent with the formation of CdS in its cubic phase (zinc blende/Hawleyite).…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…13 In this work, we study MEG in dispersions of quasi-Type II CQDs formed by the growth of a CdS shell around a InP core; in this CQD structure, the electron is delocalised over the core and shell whilst the hole is confined to the InP core, 18 as illustrated in Figure 1. InP CQDs form with a cubic crystal structure (lattice constant 5.87 Å) 19 but the thermodynamically stable phase 4 of CdS is hexagonal 18 . However, CdS can also exist in a cubic phase (lattice constant 5.83 Å) 19 which, as we show below, can form when thin shells of CdS grow on to an InP core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In type-I 1/2 (or quasi-type-II) hetero-NCs one carrier is delocalized over the whole volume of the hetero-NC, while the other is localized in one of the segments (e.g., CdSe/CdS, ZnSe/CdSe). This allows the electron-hole spatial overlap to be tailored by controlling the size, shape, and composition of each segment of the hetero-NC, which has a dramatic impact on several properties (viz., quantum yields, stability, PL wavelength [15,16,21,60,61], reabsorption cross section [22,29,[62][63][64], radiative lifetimes [60,[64][65][66], exciton-phonon coupling strength [67][68][69], Auger recombination [66,[70][71][72], hot carrier relaxation [51,73], thermal quenching [74,75]). The general trend is that the exciton lifetime, exciton-phonon coupling, and PL wavelength increase when going from the type-I to the type-II localization regimes, while Auger recombination rates and hot carrier relaxation rates are reduced.…”
Section: Composition Effects: Tailoring the Property Gamutmentioning
confidence: 99%